HYPOXIHYPOBAROTHERAPY IN REGULATION OF NEUROHUMORAL AND CYTOKINE RESPONSE IN REHABILITATION OF CHILDREN WITH BRONCHIAL ASTHMA - G.D. Alemanova (Union of pediatricians of Russia, 2009)
The effect of hypoxihypobarotherapy in children with bronchial asthma at the rehabilitation stage on the clinicals and dynamics of immunity response to the disease has been studied. Clinical efficacy of hypoxihypobarotherapy was 63,3% in moderate asthma. Positive dynamics of immunological indicators and neuropeptides have manifested in reduced of IL 4, IL 5, IL 18 and substance P serum levels. Use of hypoxihypobarotherapy in children with bronchial asthma has resulted in favourable clinical and immune dynamics and positive alteration of neurohumoral regulation mechanisms and reduced intensity of neurogenic inflammation. Determining immunological indicators, including neuropeptides, may serve as an additional criterion for assessing the efficacy of this treatment in children with bronchial asthma at the rehabilitation stage.Key words: children, bronchial asthma, pneumotherapy, hypoxihypobarotherapy, neuropeptides, cytokines.